2021
DOI: 10.1007/s10389-021-01625-8
|View full text |Cite
|
Sign up to set email alerts
|

Considering sex/gender in interventions to promote children’s and adolescents’ leisure-time physical activity: a systematic review and meta-analysis

Abstract: Aim The main objectives of this systematic review were to evaluate the effects of interventions on leisure-time PA of boys and girls and to appraise the extent to which studies have taken sex/gender into account. Subject and methods PRISMA guidelines were followed. Two researchers independently screened studies for eligibility and assessed the risk of bias. Descriptive analyses were conducted to evaluate intervention effects in relation to the consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Furthermore, leisure time activities may also take gender differences and the promotion of equal opportunities for well-being into account. Consequently, the design of interventions should address gender differences in parental engagement in leisure time [ 38 ] and differential factors influencing motivation in boys and girls [ 39 ]. Thus, Ibero-American policies to promote child well-being should consider the importance of leisure time, specifically active leisure time with family and the differential factors influencing girls and boys.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, leisure time activities may also take gender differences and the promotion of equal opportunities for well-being into account. Consequently, the design of interventions should address gender differences in parental engagement in leisure time [ 38 ] and differential factors influencing motivation in boys and girls [ 39 ]. Thus, Ibero-American policies to promote child well-being should consider the importance of leisure time, specifically active leisure time with family and the differential factors influencing girls and boys.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative studies have found the BPN of relatedness positively affects autonomous motivations to be active in PE and leisure PA settings for adolescents (Schulze et al, 2022;R. L. White et al, 2021).…”
Section: Previous Studies On Relatedness In Pamentioning
confidence: 99%
“…In PE, BPNs of autonomy and competency were affected more by the teaching environment, whereas relatedness was influenced by their peer group (Vasconcellos et al, 2020). SDT studies have found that leisure-time, nonorganized PA with peers were particularly salient to adolescent males, and gender and social identity had not been adequately considered in PA interventions (Schulze et al, 2022). A qualitative inquiry of peer motivational climate in youth sport, using content analysis to examine topics such as team competition and relatedness support, found more research was needed on the effect peers had on PA motivation (Vazou et al, 2005).…”
Section: Previous Studies On Relatedness In Pamentioning
confidence: 99%
“…Even so, as far as gender in PAL is concerned, gender is still rarely investigated in the field of preschool education. According to multiple review articles, Schlund et al (2021a), Schlund et al (2021b), Schulze et al (2021), and Kippe and Lagestad (2018) found that gender is inadequate in related studies to a large extent. Some identified affecting factors such as ethnicity (Hu et al, 2021), semester of birth (Navarro-Patón et al, 2021), and SEND also failed to be considered in the previous studies.…”
Section: Research Questionsmentioning
confidence: 99%